(untitled) (Al-Academy, 2025)
The metaphor was represented by the designer’s authentication of the design discourse through his representation of a group of important heritage and cultural symbols in the history of his society, to express his cultural and environmental identity, and this may reflect the strength of the designer’s attachment and pride in the roots, and his overwhelming desire to show the strength of identity in all aspects of fashion, as the metaphor is a mirror that reflects the imagination’s ability to monitor evidence of similarity in the universe and is a means of reshaping the universe by creating a new reality. From here, the researcher formulated her research problem by posing the following question: What are the representations of metaphor for fashion fabric designs? The research came in three chapters, as follows: The first included the research problem, while the research goal represented identifying the representations of metaphor for fashion fabric designs? The second chapter included the theoretical framework with two topics, the first topic included (the concept and patterns of metaphor), and the second topic (references of metaphor in the design of fashion fabrics). The third chapter included the most important conclusions reached by the researcher, including: - 1. Metaphor contributes to creating harmony in the production of fashion fabric design at the intellectual level through the use of creative elements and the second level is the process of producing the design idea. 2. Metaphor carries within it the imagination to create new forms based on hidden mental metaphors that are integrated into one context in the design of fashion fabrics. Keywords: representations, concept, patterns, metaphor, references.